1999
DOI: 10.1046/j.1365-2281.1999.00199.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of surface EMG during dynamic shoulder forward flexions: a study of clinically healthy subjects

Abstract: There is a shortage of studies concerning the reproducibility of surface electromyography (EMG) during dynamic contractions. The movement per se introduces factors that could have the potential to affect the characteristics of the electromyogram. The aim of this study was to investigate the during-the-day reproducibility (using intra-class coefficient, ICC) of the peak torque (PT) and the EMG variables (without removing electrodes) of dynamic shoulder forward flexions. Eleven healthy women performed three sets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
12
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
5
12
0
Order By: Relevance
“…While these findings are similar to previous research reporting intra-test ICC values for mean RMS and frequency during single-joint isokinetic tests (Larsson et al, 1999a;Larsson et al, 1999b), these previous investigations have demonstrated a smaller range of ICC values than the current study. While this may indicate greater variability in the current study, caution should be taken when comparing ICC values between separate investigations, as this statistic is largely influenced by the range of data scores and the population studied (Atkinson and Nevill, 1998).…”
Section: Reliability Of Emg Measuressupporting
confidence: 90%
See 3 more Smart Citations
“…While these findings are similar to previous research reporting intra-test ICC values for mean RMS and frequency during single-joint isokinetic tests (Larsson et al, 1999a;Larsson et al, 1999b), these previous investigations have demonstrated a smaller range of ICC values than the current study. While this may indicate greater variability in the current study, caution should be taken when comparing ICC values between separate investigations, as this statistic is largely influenced by the range of data scores and the population studied (Atkinson and Nevill, 1998).…”
Section: Reliability Of Emg Measuressupporting
confidence: 90%
“…At present, it is difficult to determine the cause of the varied reliability within certain sets, as no clear relationships are evident between the level of reliability and either the number of repetitions performed in a set, nor the intensity of the set. It is possible that the small sample size employed, although similar to previous investigations that have assessed EMG reliability (Larsson et al, 1999a;Larsson et al, 1999b), may have contributed to these findings.…”
Section: Reliability Of Emg Measuresmentioning
confidence: 76%
See 2 more Smart Citations
“…Previous kinesiologic EMG studies reported samples composed by six to thirteen subjects tested to reach objects, lift box, and flexion shoulder, obtaining good reprodutibility of results (22)(23)(24)(25). This is the first study to use kinesiologic EMG to evaluate the effect of occlusal support on masticatory, head and neck, trunk, and lower limb muscles simultaneously during complex functional tasks.…”
Section: Discussionmentioning
confidence: 91%